Solitary neurofibroma of the inferior orbit: A rare occurrence - V Sowmya; Nelly E. P. Nazareth; Ram Shenoy Basti; Nisha Marla (Wolters Kluwer Medknow Publications, 2015)
Solitary neurofibroma in the absence of neurofibromatosis is of rare occurrence and very few have been reported in the literature till now especially in the inferior orbit. A case of solitary neurofibroma of the inferior orbit is presented here. 32 year old male patient presented to us with history of swelling below the left lower lid since 2 years. After the detailed clinical and radiological examination patient underwent anterior orbitotomy and excision of the mass. Histopathological examination confirmed the diagnosis of neurofibroma of the inferior orbit which is of very rare occurrence.